محاولات هيئة إشراف اللّغة في ترقية مهارة الكلام طالبات الفصل الأول بمعهد دار السلام كونتور للبنات الحرم الثالث للتربية الإسلامية الحديثة عام 2020-2021 - Ulga Aulia Putri Jannah; Agus Yasin; Astuti Syifa’urrohmah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2023)
Darussalam Gontor Islamic Boarding School is one of the educational institutions in Indonesia that uses Arabic in daily activity. This institute chooses speaking skills as the first skill to be learned. It cannot be denied that the ability to speak is one of the most important aspects of language activities for children and adults. The linguistic competence of the new students is the main of the research is related to the speaking ability of the first grade students. Researchers found that language advisors have a special role in improving their linguistic skills through various approaches to develop them, especially in speaking skills. Therefore, the researchers specialized in their research on language counseling staff in their efforts to improve the speaking skills of first-grade students because the language advisory staff contributed quite a lot in language activities in this lodge. Therefore, the researcher wanted to know the efforts of the language advisory staff in improving the speaking skills of first-grade students at the Darussalam Gontor Islamic Boarding School of Third Campus Female at 2020-2021. Researchers used a qualitative approach with a qualitative descriptive study approach, data collection sources used were observation, interviews, and written documents. The data analysis method that the researcher uses is based on the Miles and Huberman method, namely data reduction, data presentation and analysis, then deduction. From the data analysis, it can be concluded that the program made by the language advisory staff include extracurricular activities such as muhadatsah sobahiyah, mahkamatu-l-lughoh, muhawarah sobahiyyah, idofah masa'iyyah, islah lughoh, musyahadah jama'iyyah, drama contests, and Princess and Queen of Language. This activity is a must be annual activity in this boarding school. These activities use a special approach and different methods, including direct methods, auditory and oral methods, and others. The language advisory staff acts as the main person in charge of all language activities at this lodge in and enforcing the language rules in this lodge.